Jejaling Tali Silaturahmi: Makna Hutang Pada Budaya Dan Tradisi Buwuhan Di Desa Slempit, Dusun Lingsir, Kecamatan Kedamean - Fadilah, Annisaul; Tumirin, Tumirin (Journal of Culture Accounting and Auditing, 2024)
This research aims to analyze the meaning of debt in the buwuhan culture and traditions in the community of Slempit Village, Lingsir Hamlet, Kedamean District, Gresik Regency. This research is qualitative research with a phenomenological approach. The data source used in this research is primary data source. Primary data was obtained through interviews with informants who were involved in the cultural practices and traditions of buwuhan in Slempit Village, Lingsir Hamlet, Kedamean District, Gresik Regency. Data collection techniques in this research are interviews, observation and documentation. There were five informants chosen, namely cultural figures, elders, village heads, people from duwe gawe, people who recorded buwuhan practices. The results of the research that has been carried out show four meanings of debt in the buwuhan tradition in Slempit Village, Lingsir Hamlet, Kedamean District, namely, as ties of friendship, mutual cooperation, debts and receivables in the buwuhan tradition, building a foundation of goodness and togetherness in society. The meaning of debt in the buwuhan tradition reflects the ties of friendship.